When is experiential avoidance harmful in the moment? Examining global experiential avoidance as a moderator. (December 2018) - Levin, Michael E.; Krafft, Jennifer; Pierce, Benjamin; Potts, Sarah
Abstract: Background and Objectives: Although experiential avoidance has been shown to predict a wide range of mental health problems, there has been minimal research to-date on the more immediate effects of engaging in experiential avoidance in the moment or the moderators that predict when it is more or less harmful. Methods: An ecological momentary assessment (EMA) study was conducted with 70 undergraduate students who completed assessments three times a day, over 7 day as well as a baseline assessment of global questionnaires. Results: Both greater global experiential avoidance and momentary experiential avoidance independently predicted greater momentary negative affect, lower positive affect, and lower valued action. Global experiential avoidance was also a significant moderator of momentary experiential avoidance such that experiential avoidance in the moment was more strongly related to negative effects among those high in global experiential avoidance. Limitations: Study limitations include a non-clinical student sample and use of unvalidated EMA items. Conclusions: Overall, these results suggest engaging in experiential avoidance in the moment has more negative, immediate effects particularly among those who engage in global, inflexible patterns of experiential avoidance. Highlights: Ecological momentary assessment study with 70 college students. Greater momentary experiential avoidance predicted worse affect and valued action. Global experiential avoidance moderated this relation. Momentary avoidance more strongly related to outcomes at higher global avoidance.